INNOVATIVE LEARNING PATTERNS TO IMPROVE THE QUALITY OF EDUCATION IN CLASS I AT STATE ELEMENTARY SCHOOL 24 BANDA ACEH - Ridhayanie, Ridhayanie; Syarfuni, syarfuni; Sariakin, Sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The implementation of innovative learning patterns in Elementary School 24 Banda Aceh is an effort to improve the quality of basic education through Project-Based Learning (PBL) and Game-Based Learning methods. This study uses a descriptive qualitative approach with data collection techniques through classroom observations and in-depth interviews with teachers. The results of the study indicate that this innovative method has succeeded in increasing student engagement and motivation by making learning more interactive and fun. PBL allows students to engage in real projects, improving critical thinking skills and communication skills, while Game-Based Learning facilitates conceptual understanding through game activities. Although challenges such as activity design and technological limitations were faced, the positive impact on students' understanding of the material and social skills was evident. Support from the school and parents played an important role in the success of the implementation, and plans for evaluation and development of learning methods showed a commitment to continuously improving the quality of education. This study concludes that innovation in learning can provide significant benefits for students and be a model for other schools.